Study of bone morphogenetic protein-2 delivery with different TiO2 nanotube structures - Tay, Beng Kang (2014)
A release controlled and localized carrier is important for bone morphogenetic protein delivery in order to enhance the effectiveness in bone repair. In this work, various TiO2 nanotubes with tunable morphologies are fabricated by electrochemical anodization in different organic electrolytes. Their effect on delivery of bone morphogenetic protein-2 (BMP-2) was investigated. During the protein delivery test, it was found that the nanotube structures show superhydrophilic property and tight interaction with protein, compared with the Ti flat surface. The elution profiles of TiO2 nanotube structures have shown slowed down release rate, suppressed initial burst and reduced total amount of BMP-2. The protein retention amount is over 90% for all nanotube structures. The release rate and protein retention are highly related to surface wettability: the more hydrophilic the surface, the slower the release rate and the higher the protein retention. Furthermore, a larger initial burst could be caused by a smaller nanotube density in protein release process.